Dynamics and stability issues of a synch-rotor aircraft - Avanzini, G.; Bertolani, G.; De Angelis, E.L.; Giulietti, F.; Rossetti, G. (My University, 2021)
This paper presents an analytical framework for addressing the stability analysis of a synch-rotor configuration. By linearization about some different trim conditions, a linearized model is obtained made by the decoupled longitudinal and lateral/directional dynamics. A detailed analysis of the stability derivatives and natural modes is given, showing how relevant design parameters, proper of the intermeshing rotors configuration, affect the rotorcraft dynamical behavior. A numerical test case is discussed in support of the proposed model.